7 - Social Networks as Anti-revolutionary Forces: Facebook and Political Apathy among Youth in Urban Harare, Zimbabwe - Chiweshe, Manase Kudzai (Africa Development, 2017)
The much celebrated Arab Spring has championed social media as an organizing force. This led to the celebration of a new revolutionary force for people seeking more justice and accountability from their leaders. Maghreb became the example to follow for others across Africa especially given the central role youth played in the revolts. This article questions the ability of social media to galvanize, organize and bring together youth in other parts of Africa to be actively involved in political processes within their own spaces. Using the example of urban youth in Harare, the article show that the most popular social networking site, Facebook, is anything but a site of deep political engagement. Rather, youth spent hours on the site discussing anything from fashion, gossip, sport, sex, relationships, religion and music. By removing youth from serious engagement with issues that affect their lives, social media is cultivating political apathy among Zimbabwean youth. There are little, if any, serious policy debates and discussions online. Social media alone is thus not a panacea to address youth political apathy in Africa.